Innovativeness in Science Education: An Examination of Secondary School Students’ Perceptions - Bahar Muradoğlu; Nevzat Yiğit; Ebru Mazlum Güven (Universitas Pendidikan Indonesia, 2022)
As innovation has gained importance worldwide, educating students as individuals with innovative qualities has become imperative. Therefore, identifying students' perceptions of innovativeness in science lessons has become an issue of concern. The aim of this study was to determine secondary school students' perceptions of innovativeness. The research was conducted according to the survey method. 'Perceptions of Innovative Thinking Scale,' was revised, and necessary scale development steps were followed. Accordingly, secondary school students' general innovative thinking perceptions and the relationships of the scale subdimensions with the variables were determined with single and correlational survey models. After the responses that 831 students gave to the scale were analysed, it was determined that the students' perceptions of innovativeness were high and that gender excepted, grade level, achievement in the subject of science, participation in the TÜBİTAK 4006 science fair, and the case of receiving programming training created significant differences in the subdimensions. The research findings were discussed according to the literature. It was recommended that STEM and programming be included in science courses and that teachers guide these processes.